Simulation study of single quantum channel BB84 quantum key distribution - Foong, O.-M. (Springer Verlag, 2017)
With the increasing information being shared online, the vast potential for cybercrime is a serious issue for individuals and businesses. Quantum key distribution (QKD) provides a way for distribution of secure key between two communicating parties. However, the current Quantum Key Distribution method, BB84 protocol, is prone to several weaknesses. These are Photon-Number-Splitting (PNS) attack, high Quantum Bit Error Rate (QBER), and low raw key efficiency. Thus, the objectives of this paper are to investigate the impacts of BB84 protocol towards QBER and raw key efficiencies in single quantum channel. Experiments were set up using a QKD simulator that was developed in Java NetBeans. The simulation study has reaffirmed the results of QBER and raw key efficiencies for the single quantum channel BB84 protocol. © 2018, Springer Nature Singapore Pte Ltd.